School house rock! Election collection [videorecording (DVD)] - Newall, George (George R.); Stone, Radford (Disney DVD., 2008)
A whole new generation of patriots can be inspired by the memorable songs that explain how our government is set up and how the electoral process works. Plus, keep track of the actual voting results in all 50 states.